Motivasi Intrinsik sebagai Faktor Penentu Disiplin Kerja Karyawan PT Family Aurora Nusantara - Syarifatul Wahidah; Fitria Khoirun Nisa; Rini Sugiarti; Fendy Suhariadi (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to analyze the relationship between intrinsic motivation and work discipline among employees of PT Family Aurora Nusantara, a company operating in the food and beverage (FnB) sector. Using a quantitative descriptive approach, data were collected through Likert-scale questionnaires from a total sample of 43 employees. The analysis revealed that intrinsic motivation positively and significantly influences work discipline, contributing 24.9% (R² = 0.249), with the remaining variance explained by other factors outside this study. A regression coefficient of 0.595 indicates that a one-unit increase in intrinsic motivation corresponds to a 0.595-unit increase in work discipline. The data also highlighted that higher levels of work discipline are correlated with adherence to company regulations and enhanced employee responsibility. This study emphasizes the crucial role of intrinsic motivation in fostering work discipline within the FnB sector. Companies are recommended to implement strategies such as rewards, training, and individual counseling to enhance intrinsic motivation, thereby improving operational effectiveness and employee well-being.